(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The role of corporate social responsibility on youth development is qualitative research the study showed that Corporate Social Responsibility has a significant role on youth development, business organizations carryout a successful Corporate social responsibility stakeholders assessment. The corporate social responsibility programs should be Youth entrepreneur’s motivation programs, Educational Programs and community building programs It should significantly legalized that performing Corporate social Responsibility practices be Educational programs so as they are beneficial to the youth . Also, the study further revealed that corporate social responsibility has reducing effect major youth problems such as illegal immigration, unemployment, violence and educational disparity. There is a significant relationship between corporate social responsibility and youth development in additional the study revealed that the corporate social responsibility of a business is an unconditional acceptance of business.